Pelatihan Software Mendeley Untuk Meningkatkan Kualitas Karya Tulis Mahasiswa - Fajar adi Prakoso; Nandang Bekti Karnowati; Eri Kristanto (Politeknik Negeri Cilacap, 2023)
One of the indicators of the quality of higher education is the productivity of students in writing. The main problems faced by writers and participants when conducting research scientifically are originality, plagiarism, and compiling references. Besides that, some of the obstacles faced by students in general are their inability to write in terms of language and content. This training needs to be carried out in order to minimize the practice of plagiarism and manage references through presentations, practice, and questions and answers through three stages of activity namely the preparation, implementation, and evaluation stages. This service activity is carried out online via zoom with the target participants being final stage students who are currently or will be compiling a thesis. Based on the data, there were 112 applicants from various universities. Participants considered this workshop to be very important for the preparation of the final project and to avoid plagiarism.